(3GdCUhd GdYdejI hGdYedjI aj GdeMGSHI GdMchejI (B/s - (3GdMLGhj, MSGe CHh Ydjs ((3YeGf(B: s (3OGQ GdMGeO ddfTQ(B, s, 2004)
(3GdeaGgje GdCSGSjI ddeMGSHI GdMchejI(B- (3GdfXGe GdeMGSHj GdMchej(B- (3GdehGRfI GdYGeI(B- (3GdQbGHI GdeGdjI(B.s
(3GdeQGLY U(B.371s
Keywords: (3GdeMGSHI GdJMdjdjIs; (3GdeMGSHI GdYGeIs; (3JObjb GdMSGHGJ GdMchejIs